The Search for Efficient and Stable Metal-Organic Frameworks for Photocatalysis: Atmospheric Fixation of Nitrogen - Amro M.O. Mohamed (17075260) (2022)
Recent research targets the low-pressure synthesis of ammonia via a light-initiated catalytic process. Despite the importance of materials selection for photocatalysis, computational efforts to guide candidate materials’ nomination ahead of experiments are lacking. The purpose of this study is to employ computational screening, using density functional theory and molecular simulations, to select and evaluate metal–organic frameworks (MOFs) as nitrogen fixation photocatalysts and further deduce correlations for the prediction of MOFs’ electronic properties. First, MOFs with appropriate electronic and structural properties are identified. The top candidates have been examined from the perspective of adsorption, diffusion, and mechanical and chemical stability properties. Four MOFs, Fe2Cl2(BBTA), Fe2(mDOBDC), Zn2(mDOBDC), and Ni-BTP, have been selected based on their band edges, while only Fe2Cl2(BBTA) MOF exhibited a bandgap less than 3 eV. Fe2(mDOBDC) exhibited the highest shear modulus of approximately 31 GPa. In addition, a life cycle assessment of the four MOFs showed that Ni-BTP has the lowest environmental impact. A set of 48 MOFs’ combinations are proposed for heterojunction application to enhance charge carriers’ separation. Intriguingly, we demonstrated the predictability of MOF’s bandgap and edges from MOF’s organic linker bandgap and metal node type (oxidation state and corresponding electronic configuration) for MOF families. Other Information Published in: Applied Surface Science License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.apsusc.2021.152376